Induction immunochemotherapy followed by definitive chemoradiotherapy and consolidation immunotherapy for unresectable stage III non-small cell lung cancer: a multi-institutional retrospective cohort study - Fu, Zhixue; Dong, Xin; Sun, Jiawen; Deng, Wei; Zhao, Yuting; Yang, Dan; Jiang, Leilei; Chang, Xiao; Yu, Rong; Shi, Anhui; Yu, Huiming; Wang, Jidong; et al. (Frontiers in Immunology, 2025)
BackgroundFor unresectable stage III non-small cell lung cancer (NSCLC), the standard regimen is definitive concurrent chemoradiotherapy (CRT) followed by consolidation immunotherapy. We investigated whether incorporating induction immunochemotherapy enhances the efficacy.Materials and methodsFrom June 2018 to December 2022, 294 patients with unresectable stage III NSCLC were included, who did (162, I-CRT-I group) or did not (132, CRT-I group) receive induction immunochemotherapy, followed by definitive CRT and consolidation immunotherapy. Propensity score matching (PSM) adjusted for potential confounding variables. Overall survival (OS), progression-free survival (PFS), recurrence pattern, and safety were evaluated.ResultsAfter PSM, 206 patients (103 in each group) were included. The median follow-up time was 32.3 and 44.6 months for the I-CRT-I and CRT-I group, respectively. The I-CRT-I group showed a significant improvement in OS compared with the CRT-I group (p=0.004). The median OS in the I-CRT-I group was not reached, with 1-, 2-, and 3-year OS rates of 91.3%, 80.0%, and 72.9%, respectively; the CRT-I group had a median OS of 39.3 months, with survival rates of 91.1%, 69.3%, and 52.0%, respectively. PFS (p=0.332) and local locoregional recurrence (p=0.940) were not significantly different between the groups, while significantly lower cumulative distant metastasis (DM) was noted for the I-CRT-I group (p=0.004). Prior to PSM, the adverse events rate was 96.3% and 95.5% in the I-CRT-I and CRT-I groups, respectively, with pneumonitis noted in 57.4% and 58.3%, respectively.ConclusionInduction immunochemotherapy followed by definitive CRT and consolidation immunotherapy may improve OS and decrease DM, along with manageable safety.